1999
DOI: 10.1017/s0954579499002175
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and behavioral precursors of schizophrenia

Abstract: Attentional deficits are well-established characteristics of patients with schizophrenia and their at-risk offspring, suggesting a biological connection between attention and schizophrenia. The goal of this study is to clarify the developmental role of attention in the illness. Data has been collected from 87 subjects at high and low risk for schizophrenia who have participated in the New York High-Risk Project from 1977 to the present. Individuals are considered to be at high risk if either or both of their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
168
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(178 citation statements)
references
References 5 publications
6
168
0
4
Order By: Relevance
“…Effect sizes for discrimination of schizophrenia patients from controls range from 0.45 to 3.30 (2). A longitudinal study of children of schizophrenia patients has found that those who later developed schizophrenia spectrum disorders had shown CPT deficits at age 12-13 (61). Positron emission tomography (PET) activation studies with the degraded stimulus CPT support the role of cortical-striato-thalamic pathways in the deficits observed in schizophrenia (62).…”
Section: Neurocognitive Endophenotypesmentioning
confidence: 99%
“…Effect sizes for discrimination of schizophrenia patients from controls range from 0.45 to 3.30 (2). A longitudinal study of children of schizophrenia patients has found that those who later developed schizophrenia spectrum disorders had shown CPT deficits at age 12-13 (61). Positron emission tomography (PET) activation studies with the degraded stimulus CPT support the role of cortical-striato-thalamic pathways in the deficits observed in schizophrenia (62).…”
Section: Neurocognitive Endophenotypesmentioning
confidence: 99%
“…Further, a large body of work has demonstrated that individuals with schizophrenia have deficits on a varied set of working memory tasks [e.g., 2,3] that are associated with impairments in a range of neural mechanisms [4]. There is some data to suggest that the degree of impairment in certain aspects of working memory predicts later onset of schizophrenia [5,6]. In addition, the level of working memory impairment predicts the degree of social and occupational impairment in individuals with schizophrenia [e.g., 7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive development in this syndrome may include learning difficulties (Swillen et al 1999), speech and language difficulties (Moss et al 1999 ;Glaser et al 2002), and below-average IQ (Golding-Kushner et al 1985 ;Swillen et al 1997). Verbal and executive deficits in youngsters with the deletion resemble those of other groups that at high risk for schizophrenia (Cornblatt et al 1999). Two studies suggest that a decrease in verbal IQ accompanies the onset of positive symptoms in adolescents with 22q11DS (Gothelf et al 2005 ;Debbané et al 2006a), and one study suggests that executive function deficits in affected children and adolescents could reflect genetic risk for schizophrenia (Lewandowski et al 2006).…”
Section: Introductionmentioning
confidence: 99%